Keanekaragaman Lamun di Perairan Pantai Ketapang Lombok Barat - Muh Fahruddin; Adi Suriyadin; Heri Murtawan; Bagus Dwi Hari Setyono; Ardyen Saputra; Anita Prihatini Ilyas; Muhammad Haikal Abdurachman (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2022)
Research on the diversity index, uniformity, and dominance of seagrass in Ketapang waters was carried out in November 2021. The method used in this study was a direct field experiment using a quadrant transect measuring 50x50 cm. The results showed that there were four types of seagrasses, namely Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, and Halophila ovalis. Seagrass species C. rotundata is the type found at each observation station, so it can be said that this species can live well in the characteristics of Ketapang waters. The average diversity index, uniformity, and dominance of seagrass species in Ketapang waters were dominated by C. rotundata and E. acoroides.